Issues of rational distribution of water resources under deficit conditions - Yakubov Maksadhon; Gafurov Yusufbek; Varlamova Lyudmila (E3S Web of Conferences, 2021)
Water is one expensive resource that can run out. The article discusses the issues of determining property rights, which is one of the necessary conditions for the effective functioning of the market mechanism. In Uzbekistan, the source of clean water is groundwater, which is less prone to pollution than surface water. The paper considers two systems of water consumption rights: riparian and appropriative. The features of these systems are presented. In addition, the uneven distribution of water resources across regions requires large investments in transportation through the construction of branch canals and the laying of extended water supply networks. It should be noted that the benefits of the constructed canals will vary significantly for water users depending on their location. Due to water losses when passing through the diversion canal, agents located at the beginning of the diversion canal find themselves in an advantageous position compared to other water users. At the same time, investments in the maintenance of the water distribution system, made at the beginning of the branch canal, bring benefits to all water users located downstream. One of the most well-known approaches to constructing an indicator of water scarcity is the Falkenmark water stress index.